HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT DALAM PENGGUNAAN ANTIBIOTIK TANPA RESEP DI DUA APOTEK DI KECAMATAN PANGKALAN KOTO BARU - Legianda Efendi; Ariesta Kirana Efmisa; Rido Farnandi; Aivi Yola Dwiputri (Journal of Science and Clinical Pharmacy Research, 2026)
The use of antibiotics without prescription remains a community health issue that increases the risk of bacterial resistance and reduces treatment effectiveness. This study aimed to determine the relationship between the level of knowledge and attitudes of the community regarding the use of antibiotics without prescription in two pharmacies located in Pangkalan Koto Baru District. The research employed an analytic design with a cross-sectional approach. The study involved 100 respondents selected using purposive sampling who met the inclusion criteria. Data were collected using a structured questionnaire covering sociodemographic characteristics, knowledge, and attitudes related to antibiotic use. Data were analyzed using univariate, bivariate chi-square tests, and multivariate analysis to determine the strength of associations between variables. The results showed that most respondents had a moderate level of knowledge and a positive attitude toward the use of antibiotics without prescription. Chi-square analysis indicated a significant relationship between knowledge level and community attitudes (p < 0.05). The study concluded that better knowledge is associated with more positive attitudes toward rational antibiotic use. Continuous education through pharmacies and healthcare providers is necessary to improve community awareness of appropriate antibiotic use and prevent the emergence of resistance.